Road walkers and gender issues - Justo, Jose Sterza [UNESP]; de Freitas, Cledione Jacinto [UNESP]; de Almeida, Jlia Esteves Bicalho [UNESP] (My University, 2020)
Geographic and psychosocial mobility is one of the imperative conditions in today's world and significantly affects the production of subjectivity. Based on this observation, the present study analyzes and discusses access to geographic and psychosocial mobility as a central element in gender relations, examining the case of trecheiras, women who live from city to city, with no fixed residence, and of women who are walkers on the road, who live walking along the shoulders of the highways. Through the systematic analysis of interviews with a trecheira and with another woman who is a walker in the road, it was possible to observe that the desertion to a life of wandering from city to city or by the shoulders of the highways, stems from searches of experiences of autonomy, independence and freedom against a sedentary lifestyle that devitalizes and imprisons the woman in positions of subalternity in the domestic space.
Andarilhas de estrada e questões de gênero
Keywords: Genre; Walking; Women